Community-Based Clean Water Quality Improvement Through Monitoring and Education In A Rural Area Of Karawang - Zuhri, Alifa Rahma; Pambudi, Teguh; Umam, Hilman Imadul; Putri, Fajar Amelia Rachmawati (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2025)
Surface water is the primary source of water for communities but is highly susceptible to contamination that can pose health risks. Telukambulu, a village in Karawang, West Java, faces challenges in household clean water quality. This community service activity aims to evaluate household water quality through the assessment of physical water parameters and screening using water test strips to measure chemical parameters. Analysis reveals that household water is not entirely suitable for daily needs such as drinking and cooking, with chemical parameters like pH, alkalinity, and chlorine levels being inconsistent. Community education was conducted to enhance understanding of the importance of water management, coupled with the application of simple filtration technology for water purification. This solution was designed to be easily adopted and sustainable. The program successfully raised community awareness about the importance of clean water quality and provided practical guidelines for improving household water quality. Through this approach, it is expected that the community can manage water more healthily and support better living standards.